Prevalence of the blaCTX-M and blaTEM genes among extended-spectrum beta lactamase–producing Escherichia coli isolated from broiler chickens in Indonesia - Faridah Hayyun Durrotul; Wibisono Freshindy Marissa; Wibisono Freshinta Jellia; Nisa Nabilatun; Fatimah Fatimah; Effendi Mustofa Helmi; Ugbo Emmanuel Nnabuike; Khairullah Aswin Rafif; Kurniawan Shendy Canadya; Silaen Otto Sahat Martua (Journal of Veterinary Research, 2023)
Infections of humans and animals by multidrug resistant bacteria are increasing because of the inappropriate use of antibiotics. Disease management may be more challenging if Escherichia coli produce extended-spectrum beta-lactamase (ESBL), which could cause resistance to aztreonam and third-generation cephalosporins. This study was aimed at determining the prevalence of the blaCTX-M and blaTEM genes among ESBL-producing E. coli isolated from broiler chickens in Indonesia.